2018
DOI: 10.1016/j.scitotenv.2017.12.155
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of climate change effects on mountain ecosystems through a cross-site analysis in the Alps and Apennines

Abstract: Mountain ecosystems are sensitive and reliable indicators of climate change. Long-term studies may be extremely useful in assessing the responses of high-elevation ecosystems to climate change and other anthropogenic drivers from a broad ecological perspective. Mountain research sites within the LTER (Long-Term Ecological Research) network are representative of various types of ecosystems and span a wide bioclimatic and elevational range. Here, we present a synthesis and a review of the main results from ecolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
127
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(135 citation statements)
references
References 99 publications
5
127
1
2
Order By: Relevance
“…Increasing temperatures and precipitation changes will cause severe shifts in mountainous hydrological regimes (Beniston, 2006;Eckhardt & Ulbrich, 2003;Gobiet et al, 2014) by reducing snow and ice pack (Barry, 1990;Bosson et al, 2019;Zemp et al, 2006). They will also modify the catchment land cover by enhancing thermophilic plant communities and increasing vegetation in alpine climatic belts (Gottfried et al, 2012;Rogora et al, 2018). Extreme rain events are expected to be more frequent in the Pyrenees (Gao et al, 2006) instigating more flood events.…”
Section: 1029/2019jg005142mentioning
confidence: 99%
“…Increasing temperatures and precipitation changes will cause severe shifts in mountainous hydrological regimes (Beniston, 2006;Eckhardt & Ulbrich, 2003;Gobiet et al, 2014) by reducing snow and ice pack (Barry, 1990;Bosson et al, 2019;Zemp et al, 2006). They will also modify the catchment land cover by enhancing thermophilic plant communities and increasing vegetation in alpine climatic belts (Gottfried et al, 2012;Rogora et al, 2018). Extreme rain events are expected to be more frequent in the Pyrenees (Gao et al, 2006) instigating more flood events.…”
Section: 1029/2019jg005142mentioning
confidence: 99%
“…Many studies at single sites have revealed temporal changes in species distributions, community composition, or phenology that are consistent with predictions based on climate warming (Ash, Givnish, & Waller, 2017;Bernhardt-Römermann et al, 2015;Bertrand et al, 2011;Lenoir, Gégout, Pierrat, Bontemps, & Dhôte, 2009;Rogora et al, 2018;Sproull et al, 2015). However, with observational data (i.e., most long-term studies) it is always difficult to rule out alternative causes of temporal community change, such that comparative multisite studies are needed to strengthen tests of the general hypothesis that biotic change over time has been influenced by climate warming .…”
Section: (D) (E)mentioning
confidence: 99%
“…Mountain systems are key areas of biodiversity which contain a large number of endemic and threatened species and are often recognized as global biodiversity hotspots (Körner & Spehn, ; Mittermeier, Turner, Larsen, Brooks, & Gascon, ). However, biodiversity in the mountain ecosystems is increasingly under threat because of climate change and human disturbance (Blyth, ; Rogora et al, ). Understanding the species diversity in mountainous regions is useful for biodiversity conservation and predicting the responses of species to future environmental changes (Fischer, Blaschke, & Bässler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mountain systems are key areas of biodiversity which contain a large number of endemic and threatened species and are often recognized as global biodiversity hotspots (Körner & Spehn, 2002;Mittermeier, Turner, Larsen, Brooks, & Gascon, 2011). However, biodiversity in the mountain ecosystems is increasingly under threat because of climate change and human disturbance (Blyth, 2002;Rogora et al, 2018).…”
Section: Introductionmentioning
confidence: 99%